Aelita - als morgen gestern heute war Die Zukunftsmodellierung in Jakov Protazanovs Film - Huber, Katja (Slavistische Beitraege, 1998)
For the first time in the history of young Soviet cinematography, a film promised to combine contemporary urban life and science-fiction adventures on Mars. To this day, the fame and controversy surrounding this film continue in film studies and film criticism. The constructivist stage sets and costumes by Aleksandra Ékster helped him to the predicate "extraordinary".